Radar (sentinel 1 data)-based flood mapping in Rivers State, Nigeria - M. Menegbo, Emmanuel; J. Emengini , Ebele (International Journal of Advanced Geosciences, 2023)
The existence of floods in Nigeria, a notable environmental issue, is primarily linked to human-induced causes. These are largely linked to global warming causing shifts in climate patterns. Flooding is not always a direct result of preceding factors like heavy rain or dam overflow. Instead, it is frequently triggered by human actions such as overloading main rivers or inappropriate land use. The purpose of this study was to pinpoint areas prone to flooding in Rivers State. The main goals included the development of a spatial map depicting areas susceptible to floods. The research leverages multiple data sources, Shuttle Radar Topography Mission Digital Elevation and Rivers State Administrative Map, as well as Sentinel-1 SAR data. Assessment of potential surface runoff and identifying low probability flood-prone areas was conducted through Change Detection method on Google Earth Engine platform. ArcGIS and QGIS played a significant role in assessing the vulnerability to flood risks. The primary analyses conducted involved  overlaps analysis. The study shows a vulnerability to flooding in Rivers State across a total area of 29,660 hectares, equating to 2.75% of the state's total size. This research provides important information that can aid decision-making processes in disaster preparedness, land use planning, and the implementation of effective risk reduction measures in Rivers State, and Nigeria at large. We strongly endorse the creation of Geospatial Information Systems to record the documentation of flood zones.